2003
DOI: 10.1074/jbc.m308749200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase Type 1 Induces G12/13-mediated Stress Fiber Formation, yet Promotes Growth and Survival Independent of G Protein-coupled Receptors

Abstract: Sphingosine 1-phosphate (S1P) is the ligand for a family of specific G protein-coupled receptors (GPCRs) that regulate a wide variety of important cellular functions, including growth, survival, cytoskeletal rearrangements, and cell motility. However, whether it also has an intracellular function is still a matter of great debate. Overexpression of sphingosine kinase type 1, which generated S1P, induced extensive stress fibers and impaired formation of the Src-focal adhesion kinase signaling complex, with cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 75 publications
11
125
0
Order By: Relevance
“…This mechanism of action has been shown to be highly effective in suppressing allograft rejection and autoimmune diseases in a variety of animal models [4,5] and in initial clinical trials [6,7]. As a synthetic analog of the lysophospholipid sphingosine 1-phosphate (S1P), phosphorylated FTY720 (FTY720-P) targets and activates G protein-coupled S1P receptors (S1PR), which are well characterized for their prominent functions in regulating growth-related and cytoskeleton-dependent cellular activities [8][9][10]. The current concept of FTY720-induced lymphopenia is that FTY720 modulates lymphocyte trafficking in a dual manner: acceleration of migration into secondary lymphoid organs and blocking the egress into efferent lymphatics.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism of action has been shown to be highly effective in suppressing allograft rejection and autoimmune diseases in a variety of animal models [4,5] and in initial clinical trials [6,7]. As a synthetic analog of the lysophospholipid sphingosine 1-phosphate (S1P), phosphorylated FTY720 (FTY720-P) targets and activates G protein-coupled S1P receptors (S1PR), which are well characterized for their prominent functions in regulating growth-related and cytoskeleton-dependent cellular activities [8][9][10]. The current concept of FTY720-induced lymphopenia is that FTY720 modulates lymphocyte trafficking in a dual manner: acceleration of migration into secondary lymphoid organs and blocking the egress into efferent lymphatics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of SphK1 overexpression, Olivera et al [28,29] demonstrated that administration of micromolar (but not nanomolar) concentrations of exogenous S1P suppresses apoptosis in a dose-dependent manner, and these effects were independent of S1P receptors. Similar results were published by Van Brocklyn et al…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that suppression of apoptosis by S1P is mediated via its intracellular action, many others have argued in favor of the involvement of S1P membrane receptors, making this a controversial area (for review, see Hla et al [27]). In 1999 and 2003 Olivera et al [28,29] described that overexpression of SphK1 alone markedly reduces serum deprivation-induced apoptosis in HEK293 cells, Jurkat T cells, and NIH 3T3 fibroblasts. As shown here, stimulation with CXCL4 induces an increased SphK1 expression in monocytes and rescues these cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they differ in their physiological functions [16]. While SK1 stimulates growth and survival [17,18], SK2, which contains putative BH3 domain, inhibits cell growth and enhances apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%